When Stroke Disguises as Dementia: A Case of Missed Cerebral Venous Thrombosis - Tina Moghadam Fard; Mehrnaz Hosseinzadeh; MohammadAli Shokri; Mostafa Almasi‐Dooghaee; Fatemeh Sadat Mirfazeli (Clinical Case Reports)
ABSTRACT Cerebrovascular thrombosis is among the most critical medical conditions, making early diagnosis and management crucial. Although some symptoms of cerebrovascular thrombosis are typical and lead to early diagnosis, they can sometimes present with rare and unusual symptoms, complicating the diagnostic process. Given the morbidity and mortality associated with these events, it is important to be aware of unexpected symptoms to diagnose and manage these patients more accurately and rapidly. We report a 74‐year‐old female initially misdiagnosed with Alzheimer's because of cognitive decline and disorganized speech. Her symptoms did not improve with Alzheimer's treatment. She was reevaluated by a neurologist, and her cognitive test results were impaired. Her brain MRI revealed a previously undetected left transverse sinus cerebral venous thrombosis with subcortical white matter lesions. The patient was managed acutely with subcutaneous enoxaparin and transitioned to oral rivaroxaban, resulting in significant improvement. This case report aimed to draw attention to the pitfalls of diagnosing dementia‐like syndromes in the elderly, advocating for a systematic approach to differential diagnosis. It emphasizes that a collaborative effort between psychiatrists, neurologists, radiologists, and other healthcare members is essential for accurate diagnosis and timely intervention, which can significantly alter the management and outcome for the patient.